The interplay of community, corporate, and government interests: An analysis of forest and land fires (FLFS) in South Sumatera - Andarini, Raras Nidya; Hasan, Muhammad Aqil (Interaction, Community Engagement, and Social Environment, 2025)
Background: Forest and Land Fires (FLFs) in Ogan Komering Ilir (OKI), South Sumatera, pose significant ecological challenges. Driven by government policies, plantation businesses, and community activities, these fires spread due to peatlands and dry conditions. Satellite data from CIFOR shows an increasing affected area, from 150 km² in 2020 to over 250 km² in 2023, highlighting the urgent need for intervention. Methods: This study examines the complex interplay between community and company involvement, government policies, and FFGFs in OKI using a descriptive analytic approach method to enriched by a literature review, this study delves into the historical context and current state of forest and land fires in OKI. Findings: Previous research has highlighted the adverse impacts of these fires on the environment, economy, and community well-being, to address this, our hypothesis posits that collaborative efforts involving local communities, plantation companies, and government agencies can yield effective fire prevention and management strategies. Forest and land fires in OKI District are a complex issue because they are related to the awareness of the local community, plantation company management, and local government policies. Conclusions: The necessary effort is to encourage private plantation companies to support community involvement in the form of village-level fire control institutions facilitated by the local government. Novelty/Originality of this Study: This study provides a novel approach by analyzing the role of community, plantation companies, and government policies in addressing forest and land fires (FLFs) in the Ogan Komering Ilir (OKI) District. It proposes a collaborative solution, emphasizing the involvement of local communities through village-level fire control institutions, facilitated by the local government, to improve fire prevention and management strategies.